Pengaruh Penerapan Sistem Pengendalian Internal, Pemanfaatan Sistem Informasi Akuntansi, dan Penerapan Komitmen Organisasi terhadap Kualitas Laporan Keuangan Pemerintah Daerah: Studi Empiris pada OPD Kota Medan - Naswa Aprillia Putri; Yulita Triadiarti; Muhammad Rizal; Tapi Rumondang Sari Siregar; Muhammad Ridha Habibi Z (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This study employs a quantitative approach. This study aims to examine the effect of the Implementation of Internal Control Systems, the Utilization of Accounting Information Systems, and the Implementation of Organizational Commitment on the Quality of Local Government Financial Reports in Regional Government Organizations (OPD) of Medan City. The study population consists of all Regional Government Organizations (OPD) of Medan City, with a minimum sample of 30 OPD selected using the simple random sampling technique. Research data were obtained through the distribution of questionnaires to respondents involved in local financial management. Data analysis was conducted using SPSS software through validity testing, reliability testing, classical assumption tests, multiple linear regression analysis, hypothesis testing, and the coefficient of determination (R²). The results of this study indicate that the implementation of Internal Control Systems (ICS) and organizational commitment do not have a significant effect on the quality of local government financial reports. In contrast, the utilization of Accounting Information Systems (AIS) is proven to have a positive and significant effect on the quality of local government financial reports